2003
DOI: 10.3354/meps261243
|View full text |Cite
|
Sign up to set email alerts
|

Mixed species aggregations feeding upon herring and sandlance schools in a nearshore archipelago depend on flooding tidal currents

Abstract: Tidal rips and jets are common features associated with archipelagos and complex coastlines. In habitats where rips and jets develop, energy flow to piscivorous predators is hypothesized to be strongly associated with tidal phase due to interactions between currents, plankton, and schooling planktivorous fishes (the 'tidal coupling hypothesis'). This study tests 1 component of the tidal coupling hypothesis, that the feeding activity of piscivorous predators and the availability of planktivorous fishes are both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 37 publications
1
76
1
Order By: Relevance
“…Several studies have found associations between foraging seabirds and tidally-driven oce anographic features, and some have demonstrated that temporal components of these features were important factors influencing seabird abundance and distribution (Braune & Gaskin 1982, Zamon 2003. However, the mechanism by which these features create regions of increased prey for foraging seabirds was not investigated specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found associations between foraging seabirds and tidally-driven oce anographic features, and some have demonstrated that temporal components of these features were important factors influencing seabird abundance and distribution (Braune & Gaskin 1982, Zamon 2003. However, the mechanism by which these features create regions of increased prey for foraging seabirds was not investigated specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Plankton have traditionally been assumed to become entrained within tidal structures, attracting fish and their predators such as harbour porpoises at particular tidal phases (the 'tidal coupling hypothesis'; Uda & Ishino 1958, Wolanski & Hamner 1988, Zamon 2002, 2003. However, cycles of prey behaviour and availability in these environments may be more important in attracting predators than absolute prey abundance (Zamon 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these areas are foci for intense predation events at a multiplicity of scales (Acha et al 2004, Bakun 2006 involving animals as diverse as zooplankton (Genin 2004), larval fish (Bakun 2006), predatory fish (Zamon 2003), sea birds (Davoren et al 2003, Weimerskirch et al 2004), planktivorous sharks (Sims et al 2003), and cetaceans (Atkins et al 2004). These are areas that many members of the CEM occupy during feeding or life-history migrations, and are often integral links in connectivity between units of the CEM.…”
Section: Connectivity and Predator-prey Dynamicsmentioning
confidence: 99%